Penyuluhan dan Pelatihan Pengolahan Sampah Organik dan Anorganik Menjadi Berkah di Dusun Gunung Remuk Ketapang Kalipuro Banyuwangi - Khoiruman, Muhamad; Ningrum, Nadiya Lifa; Satriyo, Galih; Istiari, Nina Ruly; Pratiwi, Yosi Mulyana; Irawan, Doni Hadi; Rohman, Saiful; Suwarso, Suwarso; Janoko, Janoko; Ahmad, Fandi; Nurdian, Yudhi Harris (Universitas Pahlawan Tuanku Tambusai, 2024)
The research aimed to assess the effectiveness of community education and training programs in enhancing public knowledge and practices regarding organic and inorganic waste management in Gunung Remuk Village, Ketapang, Kalipuro, Banyuwangi. The study utilized a participatory approach, involving workshops and training sessions focused on the 3R concept (Reduce, Reuse, Recycle). Data was gathered through surveys and direct observation before and after the intervention. The findings indicated a significant increase in awareness among participants regarding the negative impacts of improper waste disposal and the importance of segregation. Post-program assessments revealed a notable improvement in waste sorting practices at the household level, contributing to cleaner and more sustainable local environments. Furthermore, there was a noticeable reduction in waste volume disposed of improperly, highlighting the effectiveness of recycling and reuse initiatives introduced during the program. In conclusion, the study demonstrates that targeted education and training programs can effectively empower communities to actively participate in environmental preservation efforts. By enhancing knowledge and fostering behavioral changes towards sustainable waste management practices, these initiatives not only improve local environmental quality but also promote broader societal benefits. Continued support and collaboration among local governments, communities, and private sectors are crucial for sustaining and scaling such programs to achieve long-term environmental sustainability goals.